Looked after children and offending: An exploration of risk, resilience and the role of social cognition. (April 2015) - Schofield, Gillian; Biggart, Laura; Ward, Emma; Larsson, Birgit
Abstract: There have been serious concerns in the UK about the number of young people who are looked after in state care but are also young offenders. The relationship between the care system and offending is complex, since there are shared risk factors, in particular histories of poor parenting, abuse and neglect. This article reports on a mixed methods study. It focuses on findings regarding a sample of 100 young people (age 14–19), using data from file searches, psychological measures and narrative interviews. The sample was made up of three sub-samples — looked after young people who had offended, looked after young people who had not offended and young people who had offended but were not looked after. This paper presents the study's findings in relation to the characteristics and pathways of these groups. It illustrates the range and interaction of individual, family and education and activity risk and resilience factors. In particular, it highlights the role of social cognition deficits in increasing the risk of offending for young people in state care. It also identifies the significance of relationships and constructive activity in promoting resilience. Highlights: There are multiple shared risk factors for admission to care and offending. Social cognition deficits linked to maltreatment can increase risk of offending. Supportive relationships and constructive activity promote resilience.